(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bronchiectasis is an abnormal and permanent dilatation of bronchi. It may be either focal, involving airways sup plying a limited region of pulmonary parenchyma, or diffuse, involving airways in a more widespread distribution. It is a dis order that typically affects older individuals; approximately two-thirds of patients are women.